Virtual Account Performance on Student Satisfaction: An Analysis through Perceived Ease of Use and Usefulness - Wufron, Wufron; Cupiadi, Hedi; Kurniawan, Deri Alan; Dewi, Artika; Ayuni, Sri (Yayasan Sinergi Kawula Muda, 2025)
This study examines the influence of the performance of Bank Negara Indonesia (BNI) Virtual Account (VA) on the satisfaction of Garut University students in paying Single Tuition Fees (UKT). This study uses a quantitative approach with Perceived Ease of Use and Perceived Usefulness as the variables analyzed to measure the influence on VA performance and user satisfaction. The purpose of this study is to find out how the perception of convenience and usability of VA affects student satisfaction. The results show that both the perception of ease of use and the perception of technology benefits contribute significantly to the improvement of VA performance. This improvement in VA performance then has a positive impact on student satisfaction. The research also identified factors such as operational efficiency, security, integration, and customer experience as critical elements of VA performance. Most students find that using VA makes the payment process easier, reduces the time required, and improves the overall user experience. The conclusion of this study is that the perception of the convenience and benefits of VA BNI is very important in creating student satisfaction in the UKT payment process. This suggests that efforts to continuously improve the performance of VA services will contribute to higher user satisfaction.